Disrupted Ultradian Activity Rhythms and Differential Expression of Several Clock Genes in Interleukin-6-Deficient Mice - Monje, Francisco J.; Cicvaric, Ana; Acevedo Aguilar, Juan Pablo; Elbau, Immanuel; Horvath, Orsolya; Diao, Weifei; Glat, Micaela; Pollak, Daniela D. (Frontiers in Neurology, 2017)
The characteristics of the cycles of activity and rest stand out among the most intensively investigated aspects of circadian rhythmicity in humans and experimental animals. Alterations in the circadian patterns of activity and rest are strongly linked to cognitive and emotional dysfunctions in severe mental illnesses such as Alzheimer’s disease (AD) and major depression (MDD). The proinflammatory cytokine interleukin 6 (Il-6) has been prominently associated to the pathogenesis of AD and MDD. However, the potential involvement of Il-6 in the modulation of the diurnal rhythms of activity and rest have not been investigated. Here we set out to study the role of Il-6 in circadian rhythmicity through the characterization of patterns of behavioral locomotor activity in Il-6 knock-out (Il-6 KO) mice and wild-type littermate controls. Deletion of Il-6 did not alter the length of the circadian period or the amount of locomotor activity under either light-entrained or free-running conditions. IL-6 KO mice also presented a normal phase shift in response to light exposure at night. However, the temporal architecture of the behavioral rhythmicity throughout the day, as characterized by the quantity of ultradian activity bouts, was significantly impaired under light-entrained and free-running conditions in Il-6 KO. Moreover, the assessment of clock gene expression in the hippocampus, a brain region involved in AD and depression, revealed altered levels of cry1, dec2 and reverb-beta in Il-6 KO mice. These data propose that Il-6 participates in the regulation of ultradian activity/rest rhythmicity and clock gene expression in the mammalian brain. Furthermore, we propose Il-6-dependent circadian misalignment as a common pathogenetic principle in some neurodegenerative and neuropsychiatric disorders.